Sustainability Impact Assessment of Jatigede Dam in Sumedang Regency, West Java - Wahidah, Idah; Ningrum, Sinta; Halimah, Mas; Candradewini, Candradewini; Indriyani, Iin (Indonesian Association for Public Administration (IAPA), 2024)
The construction of the Jatigede Dam in Sumedang Regency plays a strategic role in water resource management for irrigation, flood control, raw water supply, hydroelectric power generation (PLTA), and tourism. However, the benefits of the Jatigede Dam have yet to be fully realized by the community, such as the suboptimal tourism infrastructure and the inefficient operation of the hydroelectric power plant. The research method used is mixed, integrating qualitative analysis. A sustainability impact assessment approach was employed to assess the impact of the Jatigede Dam, focusing on providing an analytical basis for problem-framing. The research findings indicate that the Jatigede Dam holds excellent potential for water resource management, irrigation, flood control, tourism, and hydroelectric power generation. Still, its utilization has yet to be fully optimized. Maximizing this potential through appropriate strategies, enhancing collaboration among stakeholders to create synergy, and optimizing the dam's functions by managing water inflow and outflow effectively is crucial.